A persuasão na propaganda de alimentos transgênicos: uma abordagem sistêmico-funcional - Aliotte, Juliana Fontes (2014)
This survey compares, from the critical point of view, how persuasion is used in two texts: one in favor and one against transgenic food. With this in mind, it analyzes the arguments presented to make this persuasion effective. Methodologically, the survey is based on the SFG, especially on the Appraisal system, as well as on the extensions that arose from this proposal, which will be explained herein. The ways used to persuade make use of complex procedures that take advantage of the richness of human behaviors. The act of persuading is, in general terms, an alternative to the use of physical violence, according to Breton (2003), despite a different way of physical violence exercised by coercive means. Ways to convince can also, in this perspective, be discreetly used in a way that the other person does not even notice he/she is being the object of a request. And how can one implicitly persuade the other without using words usually considered evaluative? The Systemic Functional Grammar proposes a reticular system of descriptions of semantic options to evaluate people, things and phenomena known as Appraisal that involves the notion of tokens of attitude to define the way through which the experiential meaning can be saturated in evaluative terms, that is, in interpersonal terms. This work must answer the following questions: (a) how is persuasion used in the text in favor of transgenic food and how is it used in the text against transgenic food? (b) In which situations does the explicity or the implicity of such persuasion predominate? (c) Which additional resources are used to contribute to the persuasive process?